Mediating Taiwan: Tourists’ Perceptions of Destination Image through Social Media - Rohman, Azura Zeyna (Advances in Tourism Studies, 2024)
This study examines how digital media shapes the construction and perception of Taiwan’s destination image, focusing on the interplay between online representations and tourist meaning-making. In an era where platforms such as Instagram, Facebook, and YouTube serve as primary sources of travel information, destination branding is increasingly mediated through visual storytelling and user-generated content. While Taiwan’s official tourism campaigns highlight themes of cultural heritage, natural beauty, and urban modernity, tourists and influencers contribute parallel narratives that frame the island in diverse and sometimes contested ways. Using a qualitative research design, the study conducted semi-structured interviews with twenty-five domestic and international tourists alongside content analysis of user-generated posts on Instagram and Facebook tagged with major Taiwanese destinations including Taipei 101, Sun Moon Lake, and Taroko Gorge. Thematic analysis revealed three central dynamics: first, digital media amplifies iconic imagery that reinforces a selective but powerful destination identity; second, user-generated content introduces alternative perspectives that highlight everyday life, local culture, and hidden attractions; third, tensions emerge between promotional narratives and travelers’ authentic experiences, reflecting negotiations of identity, place, and expectation. The findings contribute to debates on digital tourism by illustrating how destination image in Taiwan is not merely produced by institutions but co-created through dynamic interactions between official branding, digital platforms, and traveler narratives.